Kesejehteraan Psikologis Pada Narapidana Di Rutan Kelas IIb Situbondo - Gopar, Abdul; Mirza, Ahmad; Atiq, Choirul; Putra, Dimas Anggara (Jurnal Ilmu Bimbingan dan Konseling, 2025)
The life experienced by inmates at the Class IIB Situbondo Detention Center involves numerous psychological challenges, such as the loss of family, loss of self-control, and loss of support. This study aims to describe the psychological well-being of inmates at the Class IIB Situbondo Detention Center. This research employs a qualitative method with a field study or case study approach. The selection of research subjects was conducted using purposive sampling, while data collection techniques included observation, interviews, and documentation. Furthermore, data analysis techniques consisted of data condensation, data display, and data verification or conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The conclusions of this study indicate that the psychological well-being of female inmates at the Class IIB Situbondo Correctional Facility has not yet been optimally fulfilled due to several existing constraints. Supporting factors for the psychological well-being of female inmates include social support, positive interactions, and spirituality. Meanwhile, inhibiting factors affecting psychological well-being consist of personality traits, cultural differences, and limitations in facilities and infrastructure.